2018
DOI: 10.5005/jp-journals-10005-1530
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Effects ofTriphala, Garlic Extracts, and Chlorhexidine Mouthwashes on SalivaryStreptococcus mutansCounts and Oral Hygiene Status

Abstract: Aims and objectivesTo determine and compare the effect of triphala, chlorhexidine gluconate, and garlic extract mouthwash on salivary Streptococcus mutans count and the oral hygiene status.Materials and methodsSixty children aged 9 to 12 years were randomly allocated into the study groups of triphala mouthwash, chlorhexidine mouthwash, garlic extracts mouth-wash, and distilled water mouthwash. Examination included decayed, missing, and filled teeth (dmft)/decayed, missing, filled surface (dmfs) and DMFT/DMFS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 109 publications
1
18
0
Order By: Relevance
“…Based on the results, all the three mouthwashes exhibited the ability to inhibit the proliferation of SM, with 0.12 CHX exhibiting the highest inhibitory effect. Many studies on oral microorganisms have reported that CHX is the best mouthwash [14,15], deeming it the gold standard in the chemical treatment against SM and dental caries [1]. Consistent with the present study, other authors showed that CHX-containing mouthwashes (0.2% and 0.06% concentrates) and Total Care Listerine Zero inhibited the formation of plaque by different species of Streptococci [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the results, all the three mouthwashes exhibited the ability to inhibit the proliferation of SM, with 0.12 CHX exhibiting the highest inhibitory effect. Many studies on oral microorganisms have reported that CHX is the best mouthwash [14,15], deeming it the gold standard in the chemical treatment against SM and dental caries [1]. Consistent with the present study, other authors showed that CHX-containing mouthwashes (0.2% and 0.06% concentrates) and Total Care Listerine Zero inhibited the formation of plaque by different species of Streptococci [16].…”
Section: Discussionsupporting
confidence: 90%
“…Dental caries is still considered a major health problem in many countries [1]. The condition is the result of an interaction between specific bacteria and diet on the one hand and the tooth surface plaque.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in pre-patent periods and effect of inoculation routes and trypanosome species on peak parastemia were evaluated using two way analysis of variance (ANOVA) with inoculation routes and parasite species as factors. Means that were significantly different were identified using Tukey’s HSD post hoc analysis[30]. Differences in rates of increase in T .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the various factors that contribute to the formation of biofilm and the colonization of microorganisms in the oral cavity, the control of the biofilms in the oral cavity is considered a great challenge. As an alternative, chlorhexidine-based mouthwashes represent the most used chemical strategy for biofilm control [ 114 , [129] , [130] , [131] ]. Chlorhexidine has a large absorption spectrum, which acts on bacteria (Gram-positive and Gram-negative), yeasts, and virus.…”
Section: Biophotonics Approachesmentioning
confidence: 99%
“…In addition, this antimicrobial agent reduces 90% of bacteria for more than 7 hours [132] . However, several adverse effects are related to the continued use of chlorhexidine in the mouth, such as altered taste, discolored teeth, burning sensation [ 114 , 129 ], increased calculus formation and soft tissues discoloration [133] , [134] , [135] .…”
Section: Biophotonics Approachesmentioning
confidence: 99%